2020
DOI: 10.1108/ijoem-02-2020-603
|View full text |Cite
|
Sign up to set email alerts
|

Emerging research themes in global value chains

Abstract: Emerging research themes in global value chains Global supply chains are continually evolving and transforming the way emerging world economies do business with their developed counterparts. Developing nations are joining forces with developed nations through these rapidly transforming global value chains (GVCs) without investing in building their own; thus saving time, money and gaining access to technological innovations. Today, developing countries are exerting greater influence globally, economically and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…In addition, most studies conducted on SC collaboration are in the context of developed countries (Wiengarten et al , 2010; Soosay and Hyland, 2015; Vlachos and Dyra, 2020). The characteristics of developed countries are different from emerging markets and as a result, some of the recommendations for SC collaboration may not be applicable in emerging markets (Arora and Hartley, 2020). Thus, our study supplements the inadequacy of research on SC collaboration in the context of emerging markets.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, most studies conducted on SC collaboration are in the context of developed countries (Wiengarten et al , 2010; Soosay and Hyland, 2015; Vlachos and Dyra, 2020). The characteristics of developed countries are different from emerging markets and as a result, some of the recommendations for SC collaboration may not be applicable in emerging markets (Arora and Hartley, 2020). Thus, our study supplements the inadequacy of research on SC collaboration in the context of emerging markets.…”
Section: Discussionmentioning
confidence: 99%
“…In response to calls in the pertinent literature for research on SC collaboration in emerging markets (Flynn et al , 2014; Arora and Hartley, 2020), the findings of this research contribute to SC collaboration theory by proposing a model which underpins the driving forces and restraining forces of SC collaboration. In particular, this study pinpoints the amplification of these driving and restraining forces, based on the contextual realities of emerging markets.…”
Section: Introductionmentioning
confidence: 98%
“…manufacturing or assembling sectors) occur in the low end of GVCs (Meng et al , 2020; Meng and Ye, 2020), with a perceived lesser agility to adapt to shock (intuitively linked to lack of control). This could partly explain why developed countries’ services exports, developing countries’ goods exports and developing countries’ jobs in small firms (vs large firms) were hit harder by COVID-19 in the short run (Maliszewska et al , 2020; UNCTAD, 2020; Arora and Hartley, 2020). However, in the longer term, it was found that firms able to step in fast and capably have gained in power as non-leads and thus influence the resilience of a GVC.…”
Section: Interdependencies and Resilience Potentialmentioning
confidence: 99%
“…Due to the liabilities of being a latecomer, these firms possess lower levels of technological capabilities compared to their client firms from advanced economies (Ozturk, 2018). In addition, due to resource scarcity, lack of sophisticated demand and overall low technological knowledge available at home, these firms including vendor firms need to depend on various external mechanisms to learn from advanced economy firms and upgrade their technological capabilities (Arora and Hartley, 2020; Banerjee et al , 2015; Gubbi et al , 2010; Elia et al , 2020; Samant et al , 2020).…”
Section: Theory Developmentmentioning
confidence: 99%